Changes in High-Risk HPV Infection Prevalence and Associated Factors in Selected Rural Areas of China: A Multicenter Population-Based Study - Yu, Yan-Qin; Jiang, Ming-Yue; Dang, Le; Feng, Rui-Mei; Bangura, Mohamed S.; Chen, Wen; Qiao, You-Lin (Frontiers in Medicine, 2022)
Background: This study aims to research the infection rate of high-risk human papillomavirus (hrHPV) and its types , the detection rate of cervical lesions and the changes of associated factors with cervical cancer in China demonstration rural areas.Methods: We selected the population from China’s three demonstration rural areas (Inner Mongolia, Shan Xi and Zhejiang),9348 women aged 30 to 64 years old were invited to participate in cervical cancer screening with cytology and HPV testing. The outcomes were assessed by the infection rates of hrHPV, , the detection rate of cytological and histological lesions in the population and the associated factors of HPV infection. Results: This was a cross-sectional, population-based, and multi-center survey. A total of 9217 women age 30-64 years (45.62±8.02) were included in this study. The infection rates of hrHPV, 16, 18, 16/18 and other 12 hrHPV were 16.3%, 3.0%, 1.5%, 4.3% and 13.6% in the population, respectively. There was significant difference in the age-specific infection rate of HPV (P < 0.05). The infection rates of hrHPV, 16, 18, 16/18 and other 12 hrHPV showed a single peak infection mode, and the peak age was 56-65 years old. The age, marital status, number of live births, education level, disease history and drinking history were the risk factors of hrHPV infection. The detection rate of cytological abnormalities was 12.98% in the population, which was higher in above 56-year-old. The detection rates of CIN2+ and CIN3+ in the population were 1.45% and 0.77%, respectively. The highest incidence rate of CIN2+ and CIN3+ were 32.12% and 17.51% in 41 45 years old group. Conclusion: The infection rates of hrHPV, HPV16, 18 and 16/18 showed a single-peak infection pattern, and the peak age of infection was 56 56 years old. The risk factors of hrHPV infection were age, history of alcohol consumption, marital status, reproductive diseases, education level, and number of live births. It was recommended Cervical cancer screening in women population with the older group (> 30 years old), especially 41–45 years old group in rural areas.